PROBLEMATIKA PENGAJARAN BAHASA ARAB PADA KELAS IX MTs - nurul hidayah; Parihin Parihin; Hani Nurlaeli; Haeruman Rusandi (Matluba: Jurnal Pendidikan Bahasa dan Budaya Arab, 2023)
The purpose of this research is to find out the problems of learning Arabic in class IX Madrasah Tsanawiyah. In the world of education, especially in educational institutions, problems or problems in the field of education that they face cannot be avoided. One example is the Madrasah Tsanawiyah (MTs) which experienced problems in the implementation of education, especially in teaching Arabic in class IX. These problems or problems are caused by a lack of motivation and interest in students in Arabic, limited resources and facilities, lack of use of technology in learning, limited learning time, lack of teacher skills in teaching Arabic and lack of support and the role of parents. This research is based on the results of direct observation and interviews with several informants, and uses qualitative research methods, which are natural or holistic, which reveal the problems as they are without engineering. To achieve the educational goals listed in the GBHN, it takes seriousness and effort by teachers, students and other education actors. It is very important to get well-resourced humans